ANALISIS AKTIVITAS BELAJAR SISWA BERDASARKAN PENDEKATAN KONSTRUKTIVISME DI KELAS VII SMP NEGERI 9 BONE - Erwana; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine students’ learning activities based on the constructivist approach in class VII of SMP Negeri 9 Bone, describe the forms of students’ learning activities during the learning process, and identify the supporting and inhibiting factors in implementing the constructivist approach to improve students’ learning activities. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of teachers and seventh-grade students of SMP Negeri 9 Bone. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The results showed that the constructivist approach was able to improve students’ learning activities during the learning process. Students’ learning activities were reflected in asking questions, participating in discussions, expressing opinions, collaborating in groups, and presenting discussion results in front of the class. In addition, the constructivist approach also improved students’ self-confidence, communication skills, and critical thinking skills. Supporting factors in implementing the constructivist approach included the use of interesting learning media, active classroom atmosphere, and collaboration among students. Meanwhile, the inhibiting factors included students’ lack of confidence, differences in learning abilities, and limited learning time. The implication of this study indicates that the constructivist approach can be used as an effective learning alternative to improve students’ learning activities and create a more active, interactive, and student-centered learning process..